Strategi Komunikasi Organisasi Persatuan Mahasiswa Islam Pattani Selatan Thailand Indonesia (PMIPI) di Banda Aceh - Muhammad Syarif; Mr. Mahyeeding Dengming; Zulfadli Zulfadli; Zakaria Zakaria; Wahyu Rezeki; Mr. Nasruddin Muelee (Al-Balagh : Jurnal Komunikasi Islam, 2023)
This research is about organizational communication strategies in the Thai South Pattani Islamic Student Association in Indonesia (PMIPI) Banda Aceh. The focus of the study is related to the communication strategy of the South Patani Islamic Student Association of Thailand Indonesia (PMIPTI) organization in Banda Aceh. The aim of the research is to determine the communication strategy of the PMIPTI organization in Banda Aceh. to find out the weaknesses, strengths and challenges in the PMIPTI organizational communication strategy in Banda Aceh. The qualitative research method is descriptive qualitative. The results of PMIPTI's communication strategy research in Banda Aceh can be concluded that the aim is to produce students who are not only intellectually intelligent, but also sensitive to the social realities that occur in society. The existence of the South Patani Islamic Student Association of Thailand makes a major contribution to students, where efforts are made to develop the quality of knowledge transformation for the benefit of the people.